Tongue cancer developing after haematopoietic stem cell transplantation for treatment of acute promyelocytic leukaemia: a case report - Kitano, Hisataka; Aizawa, Souichi; Chang, Emily; Yamagata, Kanako; Takayama, Hiromasa; Kawano, Tempei (Journal of the Pakistan Medical Association, 2024)
Acute promyelocytic leukaemia (APL) is a form of acute myelogenous leukaemia. APL is characterised by anaemia due to suppression of normal haematopoiesis and infection. Haematopoietic stem cell transplantation (HSCT) is current option for the treatment of haematopoietic malignancies and is proving to be successful. Although HSCT has been effective for the treatment of haematopoietic malignant tumours, chronic graft-versus-host disease (GVHD) but secondary cancers can occur, which is a serious complication and frequently involves the oral cavity and skin. Here, we report the case of tongue cancer occurring 17 years after transplantation in a patient who developed GVHD after haematopoietic stem cell transplantation and APL remission. To the best of our knowledge, this is the first report of secondary oral cancer after HSCT with APL as the primary disease. Keywords: Chronic graft versus host disease, Haematopoietic stem cell transplantation, Oral squamous cell carcinoma, Secondary cancer.